Book Review: On the Science of Uncertainty: The Biographical Method in Social Research, by Franco Ferrarotti: https://doi.org/10.60543/ts_iss.vi10.11583 ("Temas Sociais" Journal, 2026)
The death of Franco Ferrarotti (1926–2024) lends particular urgency to rereading Sobre a ciência da incerteza: o método biográfico na investigação em ciências sociais (2013) and repositioning it within contemporary debates in the social sciences. Starting from the author’s critique of positivist hegemony, the autonomisation of technique, and the “fetishism of data”, this review examines the biographical method as an epistemological, methodological, and ethical proposal grounded in relationality, historicity, and attentive listening to research participants. The analysis brings Ferrarotti’s work into dialogue with later contributions to biographical research, particularly those concerning creative methods, vulnerability, trauma, and an ethics of care, and discusses its relevance in the face of hyper-quantification and the growing algorithmic mediation of social life. It concludes that Ferrarotti’s legacy remains crucial to a critical sociology capable of combining rigour and reflexivity without reducing the complexity of human experience to abstract indicators.
Keywords: Keywords: Biographical method; Science of uncertainty; Critique of positivism; Epistemology; Qualitative research